Implementation of VLAN and ACL for Network Security at SDIT Ibnu Hajar Bekasi - Taufik Rahman; Qori Aprianto (Universitas Nurul Jadid, 2025)
In the age of modern technology, network security is essential to ensure that educational institutions operate properly. The purpose of this research is to improve the network security of SDIT Ibnu Hajar Bekasi City by applying technologies such as Virtual Local Area Network and Access Control List. This research uses the Network Development Life Cycle (NDLC) approach, which consists of the stages of initiation, planning, design, implementation, testing, and maintenance. By using vlan network segmentation, data traffic is divided into specific groups, such as administration, computer labs, instructors, and students. For now, Acls are used to set access rights between network segments according to user needs and authorization. Simulation testing on Cisco Packet Tracer shows that the implementation of vlans and acls improves network stability and security, reduces average latency, and decreases broadcast traffic. The acl configuration results show that students cannot access the teacher and administration networks. However, teachers can still access administration and laboratories. This study shows that the use of vlans and acls can improve the security and effectiveness of network management in schools.